Importance of Insoluble-Bound Phenolics to the Antioxidant Potential Is Dictated by Source Material - Fereidoon Shahidi; Abul Hossain (MDPI AG, 2023)
Insoluble-bound phenolics (IBPs) are extensively found in the cell wall and distributed in various tissues/organs of plants, mainly cereals, legumes, and pulses. In particular, IBPs are mainly distributed in the protective tissues, such as seed coat, pericarp, and hull, and are also available in nutritional tissues, including germ, epicotyl, hypocotyl radicle, and endosperm, among others. IBPs account for 20-60% of the total phenolics in food matrices and can exceed 70% in leaves, flowers, peels, pulps, seeds, and other counterparts of fruits and vegetables, and up to 99% in cereal brans. These phenolics are mostly covalently bound to various macromolecules such as hemicellulose, cellulose, structural protein, arabinoxylan, and pectin, which can be extracted by acid, alkali, or enzymatic hydrolysis along with various thermal and non-thermal treatments. IBPs obtained from various sources exhibited a wide range of biological activities, including antioxidant, anti-inflammatory, antihypertensive, anticancer, anti-obesity, and anti-diabetic properties. In this contribution, the chemistry, distribution, biological activities, metabolism, and extraction methods of IBPs, and how they are affected by various treatments, are summarized. In particular, the effect of thermal and non-thermal processing on the release of IBPs and their antioxidant potential is discussed.